Emotional Intelligence and Well-Being of Special Education Teachers in China: The Mediating Role of Work-Engagement - Fu, Wangqian; Wang, Chonggao; Tang, Wenjun; Lu, Sha; Wang, Yan (Frontiers in Psychology, 2021)
Special education teachers’ well-being is key to their mental health and influence students’ development. The study aimed to investigate the psychological mechanism of special education teachers' well-being in China, where is of the largest number of special education teachers. We explored the role of emotional intelligence and work engagement on teachers' well-being. A total of 496 Chinese special education teachers participated in the current study. Results found that (1) the emotional intelligence, work engagement were positively associated with special education teachers’ well-being; (2) work engagement played mediating role on emotional intelligence and well-being of special education teachers. To promote the special education teachers’ well-being, suggestions for policymakers and schools are discussed.